Road to uncertainty – how virtual CT models could evaluate task specific measurement uncertainties - Binder, Felix; Wohlgemuth, Florian; Hausotte, Tino (EUSPEN Virtual International Conference - Workshop: Uncertainty in dimensional X-ray computed tomography, 2020)
Computed tomography (CT) is regularly used in industrial applications for non-destructive testing. Due to the complexity of the measurement process, analytical approaches to evaluate task specific uncertainties are currently infeasible. Available methods as described in the VDI/VDE standard 2630 Part 2.1 do not meet the criteria of scalability and cost efficiency. Therefore alternatives, like the Monte Carlo based approach described in the GUM Supplement 1, are promising to evaluate task specific uncertainties even on an industrial scale. The talk will present a basic framework for this approach and provide an inside view of the current research in this field. <
Keywords: Computed Tomography; Task Specific Measurement Uncertainty; Virtual CT